2015
DOI: 10.1108/ilt-11-2011-0095
|View full text |Cite
|
Sign up to set email alerts
|

Water lubrication of PTFE composites

Abstract: Purpose -The paper aims to present results on the friction and the wear of polytetrafluoroethylene (PTFE) and eight commercially available composites with PTFE matrix, for tests done on shoe/roller tribotester with water lubrication in open circuit. There are pointed out particular tribological processes within the superficial layers of the composites with the help of optical microscopy. Design/methodology/approach -Analysing the tribological behaviour of eight grades of PTFE composites sliding in water on sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Graphene has aroused great interest among the scientists lately, due to their special physical properties which are supposed to be transferred to composite materials [1,2,3,6]. Some polymers show low mechanical properties which can be improved by adding various types of materials [7,11]. Using nanoparticles, an enhancement of mechanical, thermal and electrical properties can be obtained, even for small contents of additives [8,9,10,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has aroused great interest among the scientists lately, due to their special physical properties which are supposed to be transferred to composite materials [1,2,3,6]. Some polymers show low mechanical properties which can be improved by adding various types of materials [7,11]. Using nanoparticles, an enhancement of mechanical, thermal and electrical properties can be obtained, even for small contents of additives [8,9,10,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Water is used as a green lubricant to replace mineral oil and vegetable oil because of its low cost, flame retardancy, easy availability, and environmental friendliness [40]. Some friction and wear experiments of different composite materials under water lubrication have been conducted [41][42][43][44][45][46][47][48]. Tomizawa and Fisher [49] found that the friction coefficient between the Si 3 N 4 ceramics with water lubrication became less than 0.002 after a running-in process, making it the first study to see that water used as a lubricant could achieve superlubricity [50].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the PTFE hydrothermal impregnation technology contributed to reducing the friction coefficient of the material and improved its anti-friction performance. [13] Furthermore, the friction coefficient of the samples slightly reduced with an increase of the sintering temperature of the copper-graphite composites, which may due to the high relative densities of the samples, which improved their overall anti-friction performances.…”
Section: Friction and Wear Propertymentioning
confidence: 97%